Exploring the Effects of Implementing TQM Strategy, With Organizational Learning Capability and Innovation Capability as Mediators, On Operational Performance at Indonesian Plastic Packaging Industry - Soesilo, Rahman; Yunus, Eddy; Ady, Sri Utami (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The purpose of this study to unravel and understand the positive correlation between TQM and OP, mediated by Organizational Learning Capability (OLC) and Organizational Innovation (OI) on the plastic packaging industry. Design/Method/Approach: The This research utilizes quantitative survey conducted across 140 plastic companies with Structural Equation Modeling Partial Least Squares (SEM PLS) analysis Research Finding: The findings reveal that as organizations implement TQM strategies, there is a discernible positive impact on Operational Performance. This relationship is intricately influenced and mediated by the organizational processes of learning and innovation. Organizational Learning Capability (OLC) and Organizational Innovation (OI) emerge as pivotal mediators, playing a vital role in shaping the dynamics between TQM and Operational Performance.